2022
DOI: 10.21660/2022.100.3630
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Geopolymer Mortar Characterization Using Fly Ash and Pumice Sand

Abstract: The cement-making process is one of the highest contributors to atmospheric CO2 levels, leading to wide consideration and analysis of alternative cement substitutes. One of the materials widely used as a substitute is fly ash, whose properties are similar to cement. It is also abundant in nature due to the combustion of coal furnaces at the Rum Steam Power Plant. Therefore, this study aims to determine the effect of heating in the geopolymer mortar treatment process. The test object was a cube mortar containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Since the fly ash arena has no unique handling process and is often placed in open areas, it is referred to as a waste that can potentially cause environmental pollution. So, fly ash material is used as a substitute for cement that contributes 2.8 million tons of CO2 gas annually and is then referred to as an alternative to environmentally friendly concrete [23]. The types of fly ash commonly used as a concrete mix are types F and C. This study used type F fly ash (low calcium fly ash) since it is economical, environmentally friendly, and has good flowability.…”
Section: Fly Ashmentioning
confidence: 99%
“…Since the fly ash arena has no unique handling process and is often placed in open areas, it is referred to as a waste that can potentially cause environmental pollution. So, fly ash material is used as a substitute for cement that contributes 2.8 million tons of CO2 gas annually and is then referred to as an alternative to environmentally friendly concrete [23]. The types of fly ash commonly used as a concrete mix are types F and C. This study used type F fly ash (low calcium fly ash) since it is economical, environmentally friendly, and has good flowability.…”
Section: Fly Ashmentioning
confidence: 99%
“…Saputra et al [13] found that International Journal of GEOMATE, Dec., 2023 Vol.25, Issue 112, pp. [21][22][23][24][25][26][27][28][29][30][31] ISSN: 2186-2982 (P), 2186-2990 (O), Japan, DOI: https://doi.org /10.21660/2023.112.4083 Geotechnique, Construction Materials and Environment applying 5% NaOH for 30 minutes reduced lignin content by 1.33% while raising cellulose levels by 22.52% in Bemban fiber. Syarief et al [4] applied 4% NaOH to Bemban fiber for 30 and 60 minutes to get a bending value of 112.24 MPa and an impact value of 0.0208 Joules/mm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their benefits, geopolymers have drawbacks, such as brittle characteristics, which need the use of a mixed material to boost tensile strength, such as fiber [21]. Natural fibers have the benefits of being cost-effective, lightweight, having a high maximum strength to weight ratio, being renewable, having a low density, and requiring little energy to process [22], and so have the potential to be employed as material admixtures in the production of geopolymers [23]. The experimental test of modified Bemban fiber for mortar geopolymer was investigated in this research in order to investigate the physical and mechanical performance of specimen.…”
Section: Introductionmentioning
confidence: 99%